Stand age model for mapping spatial distribution of rubber tree using remotely sensed data in Kedah, Malaysia - Shidiq, Iqbal Putut Ash; Ismail, Mohd Hasmadi (UTM Press, 2016)
This study attempt to develop stand age model of rubber tree by using remote sensing data. Rubber tree is one of the important biomass that has been considered as the essential part in global warming reduction plan due to its beneficial carbon sequestration capability. The spatial distribution of rubber tree based on different age was most highlighted as the focus of this study. Felda Lubuk Merbau in state of Kedah has been selected as a study area and Landsat 8 OLI-TIRS data was utilized to map rubber tree and differentiate them based on age group. The relationship between vegetation indices namely NDVI, SAVI and EVI to different age stages of rubber tree were discussed.